High Amounts of S100-Alarmins Confer Antimicrobial Activity on Human Breast Milk Targeting Pathogens Relevant in Neonatal Sepsis - Pirr, Sabine; Richter, Manuela; Fehlhaber, Beate; Pagel, Julia; Härtel, Christoph; Roth, Johannes; Vogl, Thomas; Viemann, Dorothee (Frontiers in Immunology, 2017)
Sepsis is a leading cause of perinatal mortality worldwide. Breast milk feeding is protective against neonatal sepsis but the molecular mechanisms remain unexplained. Despite various supplementations with potential bioactive components from breast milk formula feeding cannot protect from sepsis. S100-alarmins are important immunoregulators in newborns preventing excessive inflammation. At high concentrations, the S100A8/A9 protein complex also has antimicrobial properties due to its metal ion chelation capacity. To assess whether breast milk contains S100-alarmins that might mediate the sepsis-protective effect of breast milk ninety-seven human breast milk samples stratified for gestational age, mode of delivery and sampling after birth were collected and analyzed. S100A8/A9 levels were massively elevated after birth (p < 0.0005). They slowly decreased during the first month of life, then reaching levels comparable to normal values in adult serum. The concentration of S100A8/A9 in breast milk was significantly higher after term compared to preterm birth (extremely preterm, p < 0.005; moderate preterm, p < 0.05) and after vaginal delivery compared to caesarean section (p < 0.0005). In newborn s100a9-/- mice, enterally supplied S100-alarmins could be retrieved systemically in the plasma. To explore the antimicrobial activity against common causal pathogens of neonatal sepsis purified S100-alarmins and unmodified as well as S100A8/A9-depleted breast milk were used in growth inhibition tests. The high amount of S100A8/A9 proved to be an important mediator of the antimicrobial activity of breast milk, especially inhibiting the growth of manganese sensitive bacteria like Staphylococcus aureus (p < 0.00005) and group B streptococci (p < 0.005). Depletion of S100A8/A9 significantly reduced this effect (p < 0.05, respectively). The growth of Escherichia coli was also inhibited by breast milk (p < 0.00005) as well as by S100A8/A9 in culture assays (p < 0.05). But its growth in breast milk remained unaffected by the removal of S100A8/A9 and was neither dependent on manganese suggesting that the antimicrobial effects of S100A8/A9 in breast milk are primarily mediated by its manganese chelating capacity. In summary, the enteral supply of bioavailable, antimicrobially active amounts of S100-alarmins might be a promising option to protect newborns at high risk from infections and sepsis.